PENGARUH SHOPING LIFESTYLE DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING - Dindi Mandala Putra; Mimi Kurnia Nengsih (UM. Bengkulu, 2026)
This study aims to analyze the influence of Shopping Lifestyle and Store Atmosphere on Impulse Buying in clothing store consumers in Bengkulu City. The research method used is a quantitative method with a survey approach. Data were collected through observation, interviews, and questionnaires to 160 respondents who were selected using purposive sampling techniques. Data analysis was carried out through validity, reliability, classical assumptions, and multiple linear regression analysis with the help of SPSS software. The results of the study show that both Shopping Lifestyle and Store Atmosphere have a positive and significant effect on Impulse Buying, both partially and simultaneously. The t-value for Shopping Lifestyle is 12.306 and for Store Atmosphere is 7.613, both are larger than the t-table (1.975) with a significance value of < 0.05, so both variables have a partially significant effect. The F test showed an F value of 6414.348 which was much greater than the F of the table (3.05) with a significance of 0.000, so that both variables also had a simultaneous significant effect on Impulse Buying. A determination coefficient value (R²) of 0.988 indicates that 98.8% of the variation in Impulse Buying can be explained by these two independent variables, while the rest is influenced by other factors outside the study. These findings confirm the importance of marketing strategies that pay attention to consumers' shopping lifestyles and store atmosphere in encouraging impulse buying behavior. Keyword : Shopping Lifestyle, Store Atmosphere, Impluse Buying